Daily and monthly variations of the Equatorial Ionization Anomaly (EIA) over the Brazilian sector during the descending phase of the solar cycle 24 - Dias, M. A. L.; Fagundes, P. R.; Venkatesh, K.; Pillat, V. G.; Ribeiro, B. A. G.; Seemala, G. K.; Arcanjo, M. O. (My University, 2020)
It has been noticed recently that the equatorial ionization anomaly (EIA) in the Brazilian eastern, middle, and western sectors present significant longitudinal variability within a short separation due to the presence of typical magnetic field structure over South America. Therefore, the main motivation of this study is to investigate day‐to‐day and month‐to‐month characteristics of the EIA in three closely spaced longitudinal sectors over the Brazilian region during the year 2016 in the descending phase of the solar activity. These three longitudinal sectors are perpendicular to the magnetic equator at its largest declination over the globe. The EIA showed a semi annual variation in all sectors with a major maximum during the summer, a minimum during the winter, and secondary maximum during spring. In addition, the EIA shows its classical behavior with a trough around the magnetic equator and crests at low latitudes(from ±15° to ±20°). When the EIA is not developed, the maximum ionization is located around the dipequatorial latitudes and the anomaly crest is absent. The number of days within 1 year that showed clear EIA development in the west, middle, and east sectors is 248 (78.2%), 236 (74.4%), and 265 (83.6%), respectively. The undeveloped/absence of EIA is also found often during the months of winter, and the numbers of such days during 2016 in the west, middle, and east are 69 (21.8%), 81 (25.6%), and 52 (16.4%), respectively. Also, the shape, strength, extent, and lifetimes of EIA crest have shown significant variabilities between the three sectors during different seasons. Further, a comparative analysis is carried out on the variations of EIA crest and lifetime between GPS observations and IRI‐2016 model, and the results are discussed.
Keywords: Equatorial Ionization Anomaly; EIA; Solar Cycle 24